Ecological impact assessment of road networks at landscape scale using spatial road disturbance index (SPROADI) - Nematollahi, Shekoufeh; Fakheran, Sima; Soffianian, Alireza (Journal of Environmental Engineering and Landscape Management, 2017)
Development of roads can have deleterious effects on natural habitats containing species of conservation concern. Fragmentation of habitat into small, non-contiguous patches may result in dramatic population declinesthus appropriate studies quantifying ecological impacts of roads at landscape scale are essential. The main goal of this study was ecological impact assessment of roads network in Eastern part of Isfahan Province, including Abassabad wildlife refuge and Siahkouh National park, which are among the most important habitats for Asiatic Cheetah (Acinonyx jubatus venaticus) classified as Critically Endangered (CR) on the IUCN Red List. For this purpose, Spatial Road Disturbance Index (SPROADI), as a new landscape index was applied for the ecological impact assessment of the roads. This index uses three sub-indices including traffic intensity, vicinity impact and fragmentation grade to calculate the ecological impacts of road networks. Results obtained through quantifying the landscape Index (SPROADI) showed that the degree of disturbance by roads network is between 0 and 54.53. Our results also revealed that 12 percent of Abassabad wildlife and wide range of suitable habitats for Asiatic Cheetah were affected by roads, which presents a conservation concern for this critically endangered species.